Role of Hyperbaric Oxygen Therapy in Prostate Tumor Microenvironment and Cancer Stem Cell Niche - Pranathi Konda; Merrel Holley; Vinoth Kumar Lakshmanan (Annals of Urologic Oncology)
Hyperbaric oxygen therapy (HBOT), has gained attention in recent years as a potential adjunct to conventional cancer treatments, particularly in addressing tumor hypoxia which is extensively employed as a post-injury treatment, is the administration of >92% oxygen at 1.5- 3.0 ATA for 60-120 minutes. HBOT is attributed to at least five mechanisms including epigenetic regulation of gene expression, mechanical effects, bacteriostatic effects, hyperoxygenation for carbon monoxide and cyanide poisoning treatment, and restoration from hypoxia. HBOT is emerging as a promising adjunct to conventional cancer treatments, particularly in overcoming tumor hypoxia—a key feature of the tumor microenvironment (TME) that drives tumor growth, therapy resistance, and metastasis. By delivering high concentrations of oxygen under pressure, HBOT improves tissue oxygenation, potentially suppressing tumor growth, reducing hypoxia-induced resistance, and enhancing the efficacy of chemotherapy and radiotherapy. Studies have shown its anti-angiogenic effects in some tumor models and its ability to alkalize the TME. In prostate cancer, HBOT has demonstrated potential in slowing tumor growth and increasing treatment sensitivity in cell lines like DU-145 and LNCaP. Additionally, it may enhance the effectiveness of radical prostatectomy and chemotherapy by synchronizing cell cycles. Therefore, the current review highlights the key aspects of HBOT in prostate cancer therapy particularly their role addressing late radiation tissue injury (LRTI) and tumor hypoxia. We have succinctly captured the multifaceted role of HBOT in modifying the TME and comprehensive overview focuses on the advanced approaches to eliminate prostate cancer stem cells (PCSCs) and exploration of their role in anti-androgen resistance, as well as stemness-related signaling pathways and growing body of evidence supporting the potential benefits of HBOT in prostate cancer treatment. Further clinical research on HBOT could lead to significant advancements in prostate cancer treatment.